Pharmacological Modulation of Nrf2/HO-1 Signaling Pathway as a Therapeutic Target of Parkinson’s Disease - Wang, Yumin; Gao, Luyan; Chen, Jichao; Li, Qiang; Huo, Liang; Wang, Yanchao; Wang, Hongquan; Du, Jichen (Frontiers in Pharmacology, 2021)
Parkinson's disease (PD) is a complex neurodegenerative disorder featuring both motor and nonmotor symptoms associated with a progressive loss of dopaminergic neurons in the substantia nigra pars compacta. Oxidative stress have been implicated in the pathogenesis of PD. Genetic and environmental factors can produce oxidative stress which has been implicated as a core contributor to the initiation and progression of PD through the degeneration of dopaminergic neurons. The transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) orchestrate activation of multiple protective genes, including Heme oxygenase-1(HO-1), through which protects cells from oxidative stress.Nrf2 has also been shown to exert anti-inflammatory effects and modulate both mitochondrial function and biogenesis. Recently, a series of studies have reported different bioactive compounds were shown to be able to activate Nrf2/ARE can ameliorate PD-associated neurotoxin, both in animal models as well as in tissue culture.In this review, we briefly overview the sources of oxidative stress and the association between oxidative stress and the pathogenesis of PD. Then, we provided a concise overview of Nrf2/ARE pathway, and delineated the role played by activation of Nrf2/HO-1 in PD. At last, we expand our discussion to the neuroprotective effects of pharmacological modulation of Nrf2/HO-1 by bioactive compounds and the potential application of Nrf2 activators for the treatment of PD. This review suggest that pharmacological modulation of Nrf2/HO-1 signalling pathway by bioactive compounds as a therapeutic target of PD.